Study on Black Soldier Fly Maggot Production on Various Media Madefrom Cattle Faeces, Feed Waste and Wastewater Solid - Wiyatna, Muhamad Fatah; Indrijani, Heni; Utama, Dicky Tri; Marlina, Eulis Tanti; Hidayati, Yuli Astuti (Jurnal Ilmu-Ilmu Peternakan, 2026)
This study aimed to determine black soldier fly (BSF) maggot biomass production on various media made from cattle feces, feed waste, and wastewater solid from the food industry. The research method used was an experimental method with seven treatments (T1: 100% beef cattle feces, T2: 100% solid waste from the food industry, T3: 100% beef cattle feed waste, T4: 50% beef cattle feces + 50% solid waste, T5: 50% beef cattle feces + 50% beef cattle feed waste, T6: 50% solid waste + 50% beef cattle feed waste, T7: 33.33% beef cattle feces + 33.33% solid waste + 33.33% beef cattle feed waste) and three replications. The variables observed were the proximate composition of the media, the number of indigenous bacteria in the media, the BSF maggot biomass and the proximate composition of the BSF maggot. The protein, fibre and fat contents of the media ranged from 11.99% to 24.92%, 20.35% to 27.98%, and 3.45% to 3.95%, respectively. The indigenous bacteria in all the media ranged from 26.42 ± 3.30 × 1010 cfu/g to 36.57 ± 9.74 × 1010 cfu/g. The BSF maggot biomass did not significantly differ across the treatments, ranging from 195 ± 32.40 g (T1) to 223.33 ± 41.89 g (T6). The proximate composition of BSF maggots revealed that the protein content ranged from 31.04–41.04%, and the fat content ranged from 6.52–12.23%. In conclusion, beef cattle feces alone or mixed with feed waste and wastewater solids from the food industry in similar proportions can be used as growth media for BSF maggots